Postreperfusion Blood Pressure Variability After Endovascular Thrombectomy Affects Outcomes in Acute Ischemic Stroke Patients With Poor Collateral Circulation - Chang, Jun Young; Jeon, Sang-Beom; Jung, Cheolkyu; Gwak, Dong Seok; Han, Moon-Ku (Frontiers in Neurology, 2019)
Background and Purpose: We evaluated the effect of 24 h blood pressure variability (BPV) on clinical outcomes in acute ischemic stroke patients with successful recanalization after endovascular recanalization therapy (ERT). Methods: Patients with anterior circulation occlusion were evaluated if they underwent ERT based on multiphase computed tomography angiography and achieved successful recanalization (≥thrombolysis in cerebral ischemia 2b). Collateral degrees were dichotomized based on the pial arterial filling score, with a score of 0–3 defined as a poor collateral status. BPV parameters include mean, standard deviation, coefficient of variation, and variation independent of the mean (VIM) for systolic blood pressure (SBP), diastolic blood pressure (DBP), mean blood pressure, and pulse rate (PR). These parameters were measured for 24 h after ERT and were analyzed according to occlusion sites and stroke mechanisms. Associations of BPV parameters with clinical outcomes were investigated with stratification based on the baseline collateral status. Results: BPV was significantly different according to the occlusion sites and stroke mechanisms, and higher BPV was observed in patients with internal carotid artery occlusion or cardioembolic occlusion. After adjustment for confounders, most BPV parameters remained significant to predict functional outcomes at 3 months in patients with poor collateral circulation. However, no significant association was found between BPV parameters and clinical outcomes in patients with good collateral circulation. Conclusion: Postreperfusion BP management by decreasing BPV may have influence on improving clinical outcome in cases of poor collateral circulation among patients achieving successful recanalization after ERT.